METODE DISKUSI MACROMEDIA FLASH UNTUK PENINGKATAN HASIL BELAJAR ALAT UKUR MEKANIK - Tri Puji Prianto (Jurnal Taman Vokasi, 2017)
This study aims to determine the improvement of learning outcomes of mechanical measuring tools using the discussion method macromedia flash class X students SMK Ma'arif NU 1 Salam Magelang. The data collection technique uses test questions to measure initial capability and tests to measure learning of mechanical measuring instruments. The result of the research shows that (1) The use of macromedia flash discussion method influences the learning result of mechanical measuring instrument from t test with t value (0.000) smaller than t table value (0,025). (2) Based on the result of the test before and after the treatments the average score of learning result of mechanical measuring instrument increased by 10.77 points which was originally 72,01 to 82,78 and all values above KKM (Criteria Completed Minimum). (3) the average value in the treatment class is greater than the control class with the selisis of 6.89 points. It can be concluded that the macromedia flash discussion method can improve the learning outcomes of mechanical measuring instruments